PSII-20 Effects of maternal nutrient restriction during gestation on bovine serum microRNA abundance. (5th December 2019) - McCarty, Keelee J; DeCarlo, Andrea; Ricks, Ralph; Pratt, Scott; Long, Nathan
Abstract: The objective of this study was to determine the effects of maternal nutrient restriction during gestation on microRNA abundance in bovine serum. Primiparous Angus-cross cows (n = 22) were fed either control (CON; to gain 1 kg/wk) or nutrient restricted (NR; 0.55 % NEm ) diets based on National Research Council requirements. On d 30 of gestation, cows were blocked by body condition and randomly assigned to one of three diets: CON fed from d 30 to 190 (n = 8), or NR/C (n = 7) or C/NR (n = 7) fed either the CON or NR diet from d 30 to 110 followed by CON or NR from d 110 to 190 of gestation. Maternal blood samples were collected the day before harvest on 190 d of gestation. RNA was isolated from serum samples using the mirVANA microRNA Isolation kit and analyzed using a previously validated miRNA microarray of known Bos Taurus sequences. MicroRNA abundance were analyzed via ANOVA using procedures correcting for false discovery rate of the microarray data. At d 190 of gestation, 26 miRNAs observed differential (P < 0.05) abundance between treatments, in which 11 miRNAs were downregulated and 15 miRNAs were upregulated in both NR/CON and CON/NR compared to CON cows. Additionally, a set of miRNAs (bta-miR-2487_L-2R-3_1ss15CT, bta-miR-215, and bta-miR-760-5p) were differentially abundant (P < 0.04) between NR/CON and CON/NR cows. Top KEGG pathway enrichment analysis of target genes included pathways in cancer, cAMP signaling pathway, axon guidance, long term potentiation, and insulin signaling. In summary, maternal nutrient restriction observed altered miRNA abundance irrespective of the time at which the nutritional insult was induced.